Characterization of ionized lignin model compounds with α‐O‐4 linkages by positive‐ and negative‐ion mode electrospray ionization tandem mass spectrometry based on collision‐activated dissociation. (10th February 2021) - Sheng, Huaming; Tang, Weijuan; Gao, Jinshan; Riedeman, James; Hurt, Matthew; Yang, Linan; Kenttämaa, Hilkka I.
Abstract : Rationale: The biggest obstacle in the rational conversion of biomass into aromatic chemicals is the identification of unknown compounds in lignin degradation mixtures that are highly complex. As opposed to lignin degradation products with β‐O‐4 linkages, very little is known about the mass spectrometric analysis of lignin degradation products with α‐O‐4 linkages. Methods: Lignin model compounds with an α‐O‐4 and another linkage, as well as lignin model compounds with only β‐O‐4 linkages, were ionized by attachment of lithium or sodium cations under positive‐ion mode electrospray ionization (ESI) or by deprotonation in negative‐ion mode ESI in a linear quadrupole ion trap mass spectrometer. The ions were subjected to collision‐activated dissociation in multiple‐stage tandem mass spectrometry experiments to characterize their fragmentation patterns. Results: All studied compounds formed abundant sodium and lithium cation adducts in positive‐ion mode ESI with no fragmentation. Model compounds with β‐O‐4 linkages displayed stable [M − H] − ions in negative‐ion mode ESI whereas compounds with α‐O‐4 linkages only showed fragment ions. CAD of the lithiated α‐O‐4 compounds provided more structural information than CAD of sodiated compounds. However, both sodiated and lithiated compounds with α‐O‐4 linkages showed losses of monomer units at the MS 2 stage, which is useful for sequencing of lignins with this type of linkage. Conclusions: An ionization and sequencing method has been developed for lignin model compounds with α‐O‐4 linkages that spontaneously fragment upon ionization via (−)ESI.